THE EFFECTIVENESS OF COMMUNICATIVE DRILLING IN IMPROVING EIGHTH-GRADE STUDENTS’ ENGLISH PRONUNCIATION - Kasim, Nuraeni; Buhari, Buhari (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2025)
This study aims to investigate the effectiveness of communicative drilling in improving the English pronunciation skills of eighth-grade students at SMP Negeri 4 Pancarijang. A pre-experimental research design was employed, involving a single class of 22 students selected through random sampling. The research instruments consisted of a pronunciation test and a questionnaire measuring students' interest in learning pronunciation through communicative drilling. The results revealed a significant improvement in students' pronunciation ability, as indicated by the increase in mean scores from the pre-test (40.94) to the post-test (75.88). Furthermore, the analysis of students’ interest showed a high level of engagement and motivation, with 82.2% of students expressing strong or moderate interest in the learning process. Statistical analysis using a paired samples t-test confirmed that the difference between pre- and post-test scores was significant (p < 0.05). These findings suggest that communicative drilling is an effective and engaging method for enhancing students' English pronunciation. The study highlights the importance of interactive and repetitive pronunciation practice in fostering both skill development and learner motivation.